The Gap in Economic Growth from Foreign Investment and Domestic Investment across Provinces in Indonesia - Asnawi, Asnawi; Irfan, Irfan; Ramadhani, M. Fathul Chairi (SAINTIS Publishing, 2020)
The study aims to determine the effect of Foreign Investment (FDI) and Domestic Investment (PMDN) on Cross-Province Economic Growth in Indonesia in 2014-2018. This study uses secondary data with Panel and Poled data consisting of 34 provinces in Indonesia, and use the 5 years time-series data during 2014-2018. The analytical method used is the panel regression analysis method with the Fixed Effect model and poled model. The results showed that foreign investment and domestic investment had a positive and significant effect on economic growth across provinces in Indonesia. Furthermore, the results of the study show that foreign investment and domestic investment have a significant and positive effect on economic growth in 8 provinces in Indonesia, and the foreign investment has a significant and positive influence on economic growth in 9 Provinces in Indonesia. However, only North Maluku, where foreign investment has a significant and negative effect on economic growth, and domestic investment significantly and positively affects economic growth in 6 provinces in Indonesia.